Introduction - Gillian Pink; Thomas Wynn (Modern Languages Open)
This introduction to L’Écriture est la peinture de la voix: Essays in honour of Nicholas Cronk provides an overview of Nicholas Cronk’s contribution to eighteenth-century studies, along with a description of the volume’s contents.